Absolute Carrier-Envelope-Phase Dependence of Dissociative Ionization of Acetonitrile by Few-Cycle Intense Laser Pulses - Yoshii, Masaki; Matsubara, Takuya; Ando, Toshiaki; Iwasaki, Atsushi; Rathje, Tim; Paulus, Gerhard G.; Yamanouchi, Kaoru (Optics InfoBase Conference Papers, 2022)
We investigate the carrier-envelope phase dependences of the dissociative ionization processes of acetonitrile induced by intense near-IR few-cycle laser pulses based on the asymmetry in the emission direction of fragment ions.
CRIS-Team Scopus Importer:2023-04-20